SOCIO-DEMOGRAPHIC FACTORS AND THE ‘UNBANKING’ OF POLISH SOCIETY - Marlena Grzelczak (Polityki Europejskie, Finanse i Marketing)
The aim of the study was to assess the degree of advancement of non-cash trade among Polish residents/consumers and to determine the relationship between socio-demographic factors and Poles’ ‘unbankedness’. The assessment of the degree of advancement of the society’s non-cash turnover was made by means of three levels of ‘unbanking’ defined by the author of the study. On the basis of the literature review, a research hypothesis was formulated: there is a statistically significant relationship between socio-demographic characteristics and consumers’ unbankedness. The research hypothesis was verified based on the results of our research using a survey questionnaire conducted in October/November 2019 on a sample of 500 adult Poles (18 years and older). The results of the empirical study generally confirmed the statistically significant influence of sociodemographic characteristics on the level of Polish people’s unbankedness. Age, education level, netincome per capita, and type of work performed ’significantly impact the Polish population’s banking level. Variables such as gender and place of residence were found to be statistically insignificant. The study showed that 10% of the surveyed population were unbanked, while as many as 87.20% represented level 3 (full banking). The problem of transactional exclusion affects young people aged 18-24 and older people over 61. The unbanked group consisted mainly of farmers, unskilled workers, the unemployed and pensioners, while level 3 mainly included office workers, white-collar workers and skilled workers. The least exclusion is found in people of working age 25-44. People in this age bracket accounted for more than 40 per cent of the share within level 3. As educational attainment increases, people move to higher and higher levels in terms of ‘bankedness’. The research showed that the higher the net income per person, the higher the level of bankedness among Poles. The results of the study complement previous analyses and point to proposed actions for institutions promoting non-cash transactions in Polish society.